REFLECTION OF A DECADE OF PRE-MARRIAGE GUIDANCE ON FAMILY RESILIENCE IN INDONESIA - Irfan, Muhammad; Khair, Damrah; Asnawi, Habib Shulton; Firdawaty, Linda (Universitas Islam Negeri Raden Intan Lampung, 2021)
The implementation of premarital guidance is based on the fact that so many divorces occur not only among families who have been married for a long time but also experienced by new couples. The state's attention to the integrity and resilience of the household is clearly stated in Law Number 1 of 1974 article 1. This research uses a qualitative (descriptive) method with the type of library research, with a socio-historical and philosophical approach. The analytical method used is qualitative data analysis, while drawing conclusions using deductive thinking. The results of this study indicate that the substance of premarital guidance is to provide basic direction and knowledge for the realization of a sakinah, mawaddah, warahmah family so that integrity and resilience in the household are achieved. The principle of premarital marriage guidance is as an effort to prevent divorce by upholding the mandate of Law no. 1 of 1974 as a representative of the holy book al-Qur'an with the aim of marriage to achieve a happy and eternal family based on God Almighty. Premarital marriage guidance has had an effect on household resilience but still needs to be maximized due to the fact that the divorce rate from year to year has increased. Keywords: Marriage Guidance, Pre-Marriage, Family Resilience.